Musical expertise facilitates statistical learning of rhythm and the perceptive uncertainty: A cross-cultural study. (September 2020) - Daikoku, Tatsuya; Yumoto, Masato
Abstract: The brain extracts statistical regularities from sequential information around our environment. This is referred to as statistical learning (SL). Statistical learning is considered an innate function in the human brain and contributes to the brain's development. Within the framework of predictive coding, this learning system allows us to predict a future state to minimize sensory reaction and resolve uncertainty around the world. By auditory statistical learning, over the brain's development, humans become able to comprehend language and music. An increasing number of studies has revealed that Western-classical musical training optimizes the brain's probabilistic model of music and enhances the accuracy of perceptive uncertainty (entropy) in newly encountered melody. No study, however, investigates how musical training modulates the probabilistic model of rhythm, and how the musical culture tunes them. The present study investigated how SL of temporal sequences with and without a beat is reflected in neural responses, and how the SL is modulated by the two types of musical training in different cultures: Western- and Japanese-classical music (i.e., Hougaku). The neural representation showed evidence that the SL effects of beat sequence were prominent in the left hemisphere. This finding was larger in Western- and Japanese-classical musicians compared with non-musicians. Further, the entropy (uncertainty) of the sequences negatively correlated with neural effects of SL, mainly in the left hemisphere of the both Western- and Japanese-classical musicians. These suggest that, regardless of musical culture, musical training may generally facilitate SL of rhythm. However, the specific neural components showed differences between groups of musicians: an earlier component, referred to as P1, represented the left lateralization for perceptive uncertainty in both groups of musicians, whereas a later component, referred to as N1, represented the left lateralization only in Japanese Classical musicians. These findings may suggest that the types of musical training differently modulate neural representation of underlying temporal SL, particularly global processing of uncertainty rather than local processing of transitional probability. The present study sheds new light on the neurophysiological account of Japanese classical music. Highlights: We examined how statistical learning of rhythm is reflected in neural responses. Musical expertise facilitates the learning of temporal transitional probability. The types of musical culture (Western vs. Japanese) differently modulate perceptive uncertainty. This study sheds light on the neurophysiological account of Japanese classical music.